Pengembangan UMKM jamu tradisional di Dusun Talun Desa Kesamben Kabupaten Malang - Khotimah, Nur; Sholikah, Ainun Ni’matus; Fi’liyah, Ma’rifatul; Magfiroh, Nila; Aryani, Lilis; Salim, Muhammad; Faizul, Muhammad Nadhif; Nazky, Afrizal (Maliki Interdisciplinary Journal, 2023)
Public dedication aimed at improving the development of quality and productivity of the community in Kesamben Village mainly in development of UMKM. In the Kesamben Village, mainly in the Talun Distric, the Kidang Talun UMKM has been established to produce jamu. These UMKM lacks knowledge about their product marketing strategy. Understanding how to market and brand is important to increase product sales. Branding is the giving of a name, term, sign, symbol, design, or combination of all, made with the purpose of identifying a product to distinguish it from a competitor’s goods or services. The implementation of this activity is by using the method of interviews, field jumping, stage editing and video upload as well as the dissemination of video branding to disseminate information and promote about UMKM jamu in Kesamben Village. Video Branding is one of the solutions to promote and introduce UMKM to the everyone, where this video can be easily accessed with the increasingly sophisticated technological developments today. With the presence of various social media platforms in the era of technological development that is growing and becoming more widespread and popular in the present time, making Video branding an alternative means quite suitable for UMKM marketing.